Editorial - Alfred Twardecki; Alla Buiskykh (Archaeologia Polona)
We are presenting to readers a volume of Archaeologia Polona containing a collection of articles resulting from excavations conducted by a Ukrainian-Polish team in the years 2018–2021 in the ancient centre of Olbia Pontica on the north coast of the Black Sea. The excavations were a joint initiative of both the Institute of Archaeology of the National Academy of Sciences of Ukraine and the Institute of Archaeology and Ethnology Polish Academy of Sciences. The aim of this volume is to present the results of the recent archaeological campaign led by prof. Dr. Alla Buiskykh and Dr. Alfred Twardecki in the broader context of our knowledge about the areas neighbouring Olbia.